Molecular cloning of the 3' half of the Clostridium perfringens enterotoxin gene and demonstration that this region encodes receptor-binding activity. - Hanna, P C (1989)
Clostridium perfringens type A enterotoxin (CPE) causes the symptoms associated with C. perfringens food poisoning. To determine whether the C-terminal half of CPE contains receptor-binding activity, the 3' half of the cpe structural gene was cloned with an Escherichia coli expression vector system. E. coli lysates containing the expressed C-terminal CPE fragment (CPEfrag) were then assayed for CPE-like serologic, receptor-binding, and cytotoxic activities. CPEfrag was shown to contain an epitope located at or near the receptor-binding domain of the CPE molecule. Competitive-binding studies showed specific competition for CPE receptors between CPE and CPEfrag lysates. CPEfrag lysates did not cause cytotoxicity in Vero (African green monkey kidney) cells. However, preincubation with CPEfrag lysates specifically protected Vero cells from subsequent CPE challenge. This indicates that CPEfrag recognizes the physiologic receptor which mediates CPE cytotoxicity. Collectively, these studies indicate that the C-terminal half of CPE contains a receptor-binding domain but additional amino acid sequences appear to be required for CPE cytotoxicity.